Notas acerca de la "Tetragamia" de León VI, el sabio - Ossandón Widow, María E. (Byzantion Nea Hellás, 2015)
The Bizantine emperor Leo VI, who reigned between 866 and 912 AD was a disciple of Focius and acquired a great classic culture, as well as an almost enciclopedic knowledge. He also was a compassionate man, but in his private life he was not very lucky. He became widower three consecutive times. After the death of his third wife, he gol married once again. The church did not accept that, since it was not allowed to gel married after the spouse’ s death. On the other hand, divorce was permitted by the civil law. This fact itself was a contradiction, for divorce is a dissolved bond. In widowhood, the link has finished sin ce one of the spouses has died. The authoress studies the difficulties caused by the second and third Leon’s marriages, and the legislation dictated by him, which allowed a third marriage. He gol the grace and married Eudocia Baiane, his third wife. But she soon died, too. Longing for a son who can be his inheritor, Leon got married for the fourth time. But now the priest who acted in the wedding was removed and the emperor was punished: he could no longer gel into the holly places. After Leon’ s death, his wife was cast out. There was di vis ion between the priests and reprisals against !hose who hadjustified the fourth marriage. The authoress shows in an annex four Leon’s laws related to marriage.